Ultrasound Diagnosis of Cubital Tunnel Syndrome in the Accessory Anconeus Epitrochlearis Muscle (Case Report) - Haiko, O.G.; Luchko, R.V.; Klymchuk, L.I. (TERRA ORTHOPAEDICA, 2022)
Summary. A case of diagnosing the accessory anconeus epitrochlearis muscle, which caused compression of the ulnar nerve and was the cause of cubital tunnel syndrome, is presented. Ultrasound is an important diagnostic method, which allows preventing unnecessary medical manipulations and choosing the right treatment algorithm.